Purified glycerin in balanced diets of broiler chickens treated from 1 to 42 days of age - Silva,Mônica Calixto da (2019)
ABSTRACT We evaluated the technical feasibility of purified glycerin inclusion in balanced diets of broiler chickens treated from 1 to 42 days of age. A total of 240 broiler chickens were distributed in a completely randomized design into four treatments (0, 2, 4, and 6% purified glycerin inclusion), with six replicates of 10 broilers each. We evaluated productive performance (at 7, 21, and 42 days), edible viscera (heart, liver, and gizzard), carcass yield and cuts, color, chemical and physical composition, as well as protein and fat deposition in the breast muscle. Dietary inclusion of purified glycerin reduced feed conversion and increased feed intake, weight gain, and weight at seven days. From 1 to 21 days, there was a decrease in feed conversion and a linear increase in weight gain, with no effect on feed intake. Considering the total experimental period, increasing glycerin levels increased weight gain and weight at 42 days, with no effects on feed conversion or feed intake. Similarly, there was no effect on carcass and cut yields, liver and gizzard yields, and weight or length of the intestine, while heart yield was decreased. There was a linear increase in crude protein, ether extract, protein, and fat deposition and a reduction in moisture percentages, with no effect on ash content. Purified glycerin levels did not affect a*, b*, L*, pH, temperature, shear force, or weight loss by cooking in breast meat. The dietary inclusion of purified glycerin of up to 6% proved to be technically feasible in the diets of broilers from 1 to 42 days.